Electromagnetic Noise Calculation of Permanent Magnet Synchronous Motor Fed by Inverter - Jun PENG; Weiye LI; Jianghua FENG; Zhichu CHEN (机车电传动)
A method for calculating electromagnetic noise of permanent magnet synchronous motor (PMSM) was presented. The electromagnetic force wave in air gap was simulated by 2D electromagnetic field finite element method. The stator single-loop structure model was established to calculate the harmonic response vibration velocity of the stator structure under electromagnetic force wave. The stator outer circle was equivalent to the effective long cylinder model to calculate the sound power level noise. The electromagnetic noise caused by inverter SVPWM power supply was calculated. The test data of the prototype was compared with the calculated value. The calculation method could satisfy the engineer requirement.